2002
DOI: 10.1038/sj.eye.6700208
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic ocular findings in Asian children with Down syndrome

Abstract: Aims/Purpose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
89
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 16 publications
16
89
4
3
Order By: Relevance
“…Historically, the prevalence of strabismus in the population with Down syndrome has ranged from 20 to 45%. 15,16 Despite this relatively high prevalence of strabismus, most of our patients (40/72 [55%]) needed no intervention because in these children the strabismus was latent or insignificant. In addition, parents did not view cosmetic correction as a high priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the prevalence of strabismus in the population with Down syndrome has ranged from 20 to 45%. 15,16 Despite this relatively high prevalence of strabismus, most of our patients (40/72 [55%]) needed no intervention because in these children the strabismus was latent or insignificant. In addition, parents did not view cosmetic correction as a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Fine, rapid horizontal nystagmus is known to occur frequently in patients with Down syndrome and needs no specific investigation or intervention. 13 In most of our patients, the nystagmus was stable or there was spontaneous resolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with numerous ocular manifestations, including eyelid problems, keratoconus, Brushfield spots of the iris, refractive error, strabismus, and nystagmus. 1,2 Many studies have reported an increasing prevalence of refractive errors with age in patients with Down syndrome. 3,4 The prevalence of strabismus in these patients has been reported to be between 19 and 70%, with esotropia representing the vast majority of strabismus cases.…”
Section: Introductionmentioning
confidence: 99%
“…In most recent studies conducted in Asia, the prevalence of glaucoma in Down syndrome ranges from 0.4% to 1% of cases, although in one series in Malaysian Down syndrome children, the prevalence was reported to be 6.7%. [5][6][7] The commonest ocular associations of Down syndrome that are reported in the Malaysian studies are include epicanthic fold (96.7%), nystagmus (33.3%) and strabismus (26.7%). Other findings were bilateral congenital cataract (13.3%) blepharoconjunctivitis (10.0%), eyelid abnormalities (6.7%) nasolacrimal duct obstruction (3.3%) bilateral retinoblastoma (1.7%), bilateral retinal detachment (1.8%) and chronic uveitis (1.7%).…”
Section: Discussionmentioning
confidence: 99%